Analysis of Seller’s Rights in Determining the Highest Retail Price (Het) of Bulk Cooking Oil from Perspective of Ibnu Taimiyah (Case Study in Sei Sikambing Village C. Ii Medan Helvetia District, Medan) - Gunawan, Indra; Marlina Tarigan, Tetty (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study aims to determine the rights of the seller and the cause of the increase in cooking oil as well as the right of the seller to determine the highest retail price by the government according to Ibnu Taimiyah. This research is qualitative research (field research) with a case study approach. The results of the study show that the factors that increase the price of cooking oil occur naturally, such as a decrease in the production of crude palm oil, high prices of crude palm oil, and the transfer of crude palm oil to CPO biodiesel. The price increase application is based on economic principles, so there should be no price-fixing according to Ibn Taimiyah, because it violates the seller’s right to determine the price according to market mechanisms.